Enniatin B and beauvericin affect intestinal cell function and hematological processes in Atlantic salmon (Salmo salar) after acute exposure. (February 2023) - Søderstrøm, Sofie; Søfteland, Liv; Sele, Veronika; Lundebye, Anne-Katrine; Berntssen, Marc HG.; Lie, Kai K.
Abstract: Unintentional use of mold-infested plant-based feed ingredients are sources of mycotoxins in fish feeds. The presence of the emerging mycotoxins ENNB and BEA in Norwegian commercial fish feeds and plant-based feed ingredients has raised concerns regarding the health effects on farmed Atlantic salmon ( Salmon salar ). Atlantic salmon pre-smolts were exposed to non-lethal doses of BEA and ENNB (ctrl, 50 and 500 μg/kg feed for 12 h), after which total RNA sequencing of the intestine and liver was carried out to evaluate gut health and identify possible hepatological changes after acute dietary exposure. ENNB and BEA did not trigger acute toxicity, however ENNB caused the onset of pathways linked to acute intestinal inflammation and BEA exposures caused the onset of hepatic hematological disruption. The prevalence and concentration of ENNB found in today's commercial feed could affect the fish health if consumed over a longer time-period. Highlights: Both BEA and ENNB elicited effects on transcription in the intestine. ENNB triggered acute inflammatory signaling in the intestine. BEA exerted greater transcriptional effects in the liver contra the intestine. BEA negatively affected heme biosynthesis and blood homeostasis in the liver.